Polarized training is not optimal for endurance athletes - Burnley, M.; Bearden, S. E.; Jones, A. M. (Medicine & Science in Sports & Exercise, 2022)
We emphasize that an "optimal" endurance training pro gram will 1) provide the necessary total training volume for the individual athlete in relation to the event being trained for and 2) appropriately balance training intensity distribution across the three zones. Polarized distributions of training vol ume have neither been shown to be more effective than other distributions, nor are they practiced commonly by endurance athletes; indeed pyramidal distributions are what highly suc cessful athletes typically practice. To be clear, we are not ad vocating a model of endurance training that emphasizes threshold training over other training intensities but rather one that appreciates the strategic value of zone 2 training in a varied and balanced overall program. In summary, polarized training was initially misrepresented and has continued to be misconstrued, and adherence to its practice is, for the most part, misguided